Process intensification approach for design and optimization of biodiesel production from palm fatty acid distillate - Karittha Im-orb; Amornchai Arpornwichanop; Lida Simasatitkul (Biotechnology Reports, 2021)
. The intensified esterification - transesterification process offers higher biodiesel yield and consumes less energy compared with the intensified hydrolysis - esterification process. The economic analysis shows that the intensified esterification-transesterification process is found to be economically feasible. Finally, environment assessment based on life cycle analysis (LCA) indicates that the environmental impact of both processes are similar.
Keywords: Biodiesel Production and Applications; Process Optimization and Integration; Lubricants and Their Additives